Effect of period of receptivity and air temperature on parthenocarpic phenomenon of ‘Assiane’ date palm cultivar (Phoenix dactylifera L.) - Zahiri, Imane; Alla, Fouzia; Alzain, Mashail N.; Alhalmi, Abdulsalam; Noman, Omar; Parvez, Mohammed Khalid; Elhoumaizi, Mohammed Aziz (Frontiers in Sustainable Food Systems, 2023)
In hot arid regions, the productivity of certain date palm cultivars faces a significant challenge wherein non-fertilized flowers can give rise to parthenocarpic singular or triplet fruit. In this study, we aimed to investigate the impact of delayed pollination on date palm yield and fruit quality, while also examining the influence of temperature on these processes. We conducted this research using ten 15year-old 'Assiane' palm trees, all situated within the Figuig Oasis environment. Pollination was performed on the same day of spathe opening, as well as up to sixteen days after the initial opening. Additionally, we utilized thirty palm trees to analyze the effect of daily average temperatures. Our findings reveal that the optimal period for achieving maximum yield and fruit quality falls between the sixth and eighth day following the cracking of the female spathe. Furthermore, we observed that relatively lower temperatures, ranging from 5 to 20°C, promote the formation of parthenocarpic fruits while inhibiting the development of normal fruits. Moreover, the insights gained from investigating this issues could have broader implications for date palm cultivation in arid regions and offer valuable lessons for the preservation of oasis ecosystems worldwide.